D'infirmière vers professeur des écoles : reconversion professionnelle et identité personnelle - Agnès Guillot; Soazig Lanoë (Nantes Université, 2011)
A quarter of the nurses suffer from professional exhaustion. Resigning and conversion in this professional area, if frequent, are not much observed. A monographic study, analyzing the career of a nurse who became primary school teacher, allowed us to understand the dynamic of her professional change, and the recomposition of her professional identity, grounded in highly personal values. A destabilisation of her self-skill feeling was determining in her decision to engage in a deliberate professional change, her self-esteem being challenged by professional wearing down and by the confrontation to her patients' death. She has been able for reconstruct both her self-esteem and skill feeling, and to reveal nursing skills reinvested as a teacher. Supported by her original institution, and by a "significant other", she prepared her profession change project and engaged in it, faithful to her identifications and to herself. This study is predicated on an ascending approach and a reciprocal analysis of different corpus, including clinical interviews and questionnaires analyzing the careers. It is based on the first professional occupation and its pressures, the decision-making process about the reconversion as a teacher and its conditions, as well as the different phases of the deliberate professional change.